Single-Vendor and Multi Buyers of Supply Chain Management under Fuzzy Environment: Optimizing Supply Chain Management in a Fuzzy Environment with Single-Vendor and Multi-Buyers (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The players (vendors, retailers, distributors, etc.) in a supply chain may belong to different corporate entities and be more interested in minimizing their own cost rather than that of the chain as a whole. This kind of single-sided optimal strategy is not suitable for today’s global competitive environment. In real life, there are many examples in which a manufacturer (here as vendor) has own set of direct outlets (here as buyers) to route the produced item to end customers. A production model for deteriorating items with the fuzzy costs has been developed taking into account the views of both the vendor and the multi-buyers.